Science, Environment, Technology, and Society - Based Module to Improve Critical Thinking in Class IV Elementary School Learning - Adriyono, Uhori; Rohman, Fatkhur; Pargito (Universitas Pendidikan Ganesha, 2023)
The low ability of Indonesian students is related to the learning process (especially science learning) which does not fully provide opportunities for students to develop critical reasoning abilities. This research aims to create a SETS-based module to improve students' critical thinking. This research is a type of Research and Development (R&D) research, the development was carried out referring to Borg & Gall's theory. The population of this study was fourth grade elementary school students. The subjects in this research were determined using a purposive sampling technique and obtained 24 students. Data collection tools use valid and reliable test instruments. The analysis technique used is quantitative and qualitative analysis. The research results show that the module is in the very valid and practical category. Material experts received a score of 0.92, media experts 0.87, language experts 0.93 and pedagogy experts 0.93, overall, in the valid category. The results of the user response assessment from students were 96.4 and teacher practicality was 93.61, including the very practical category). Data uses N-Gain with a calculation result of 0.52. The conclusion shows that the SETS-based module developed is effective in improving elementary school students' critical thinking.